A CRITICAL STUDY OF MISINTERPRETATIONS OF PROPHETIC HADITH ON DISABILITY - Umi Khofifah, Intan; Khanifah, Rizky Nur; Romadhon, Rohmat Ilham (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: This study critically analyzes misinterpretations of hadiths related to disability, which often lead to the stigmatization of persons with disabilities. Using a thematic (mawḍū‘ī) analysis of hadiths concerning the obligation to seek knowledge (ṭalab al-‘ilm) and the Prophet’s treatment of people with disabilities. Purpose of the Study; this research reveals that Islamic teachings strongly support inclusive education. The study demonstrates that universal hadiths on knowledge and the rejection of judgments based on physical appearance provide a theological foundation for inclusive education policies. Conclusion: These findings emphasize the need for a correct understanding of these hadiths in order to shape inclusive and equitable education policies in Indonesia.